2015
DOI: 10.1016/j.scitotenv.2015.05.073
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the presence of Bt-transgenic oilseed rape in wild mustard populations on the rhizosphere nematode and microbial communities

Abstract: The adventitious presence of transgenic crops in wild plant populations is of ecological and regulatory concern. In this context, their effects on non-target, below-ground organisms are not well understood. Here, we introduced, at various frequencies, Bt-transgenic oilseed rape (OSR, Brassica napus) into wild mustard (Brassica juncea) populations in the presence and absence of the target herbivore (Plutella xylostella). The impacts on soil nematode and microbial communities were assessed in this system. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
(76 reference statements)
1
13
1
1
Order By: Relevance
“…Li and Liu 13 found that the richness and diversity of nematode were not significantly altered by Bt cotton. Similar results were reported on herbivory nematode 14 , earthworm and protozoa 15 . Besides, a few studies pointed out that Bt crops did not significantly change soil microbial biomass 16 or soil enzymatic activities 1719 .…”
Section: Introductionsupporting
confidence: 89%
“…Li and Liu 13 found that the richness and diversity of nematode were not significantly altered by Bt cotton. Similar results were reported on herbivory nematode 14 , earthworm and protozoa 15 . Besides, a few studies pointed out that Bt crops did not significantly change soil microbial biomass 16 or soil enzymatic activities 1719 .…”
Section: Introductionsupporting
confidence: 89%
“…Indeed, the number of genera detected in this study exceed that recorded in previous GM-related studies that relied solely on morphological identification [42, 58]. Similarly, alternative DNA-based detection techniques (e.g.…”
Section: Discussioncontrasting
confidence: 57%
“…As GM oilseed production increases abroad, the probability of imported GM oilseed rape escaping in Europe will increase, raising environmental biosafety concerns. Environmental risks posed by GM oilseed rape include the effects of insecticidal Bt proteins expressed into GM crops on non‐target organisms (Manachini et al ., , ; Liu et al ., ), and the effects of the herbicides used in tandem with herbicide‐tolerant GM (GMHT) oilseed rape.…”
Section: Introductionmentioning
confidence: 99%